(untitled) (Journal Of Educational and Psychological Researches, 2022)
The present study is meant to inquire about the training needs of middle stage leaders in Bisha, (Saudi Arabia) from the perspective of teachers. To achieve this purpose, the researcher has designed a questionnaire containing (31) items, distributed to a sample of (157) teacher (male and female) from the target population. This research has demonstrated that the level of training needs for middle stage leaders was moderately reported with an arithmetic mean equivalent to (2.42), and a standard deviation of (0.36). Results have shown no significant differences at (α=0.05) in the sample’s expectations of the study’s variables. The study concludes with a list of recommendations such as working on developing training programs for middle stage leaders, specifically in Bisha, in order to increase their academic and professional levels. Likewise, this study emphasizes the necessity of coordination among the different parts of the educational system in order to determine the special training needs of all the workers at the Ministry of Education in the Kingdom of Saudi Arabia.